Optical solitons for the concatenation model with fractional temporal evolution - Ahmed H. Arnous; Muhammad Amin S. Murad; Anjan Biswas; Yakup Yildirim; Puiu Lucian Georgescu; Luminita Moraru; Anwar Jaafar Mohamad Jawad; Layth Hussein (Ain Shams Engineering Journal, 2025)
This paper recovers the optical solitons for the concatenation model that comes with fractional temporal evolution and Kerr–law of self–phase modulation by the usage of the enhanced direct algebraic approach. This study goes beyond previous efforts by incorporating fractional temporal evolution instead of linear temporal evolution in the concatenation model. This would facilitate the regulation of the internet bottleneck phenomenon by enabling the deceleration of internet traffic in one direction at a node while maintaining its full flow in the other direction. The model presents a novel approach that contributes to a deeper understanding of potential applications in the telecommunication industry. The implemented technique presents several solitons. In addition to those solitons, the method presents solutions in terms of Jacobi and Weierstrass elliptic functions. A full spectrum of optical solitons are thus recovered. This will include bright solitons, dark solitons, singular solitons, and straddled solitons. The existence criteria of such solitons, in the form of parameters constraints, that naturally emerged during the course of derivation, are presented. The recovered solitons will be presented in the paper that can be efficiently implemented to mitigate the internet bottleneck effect. A few numerical simulations supplement the mathematical analysis.